Determinant factors of cardiorespiratory fitness in Portuguese adolescents of different ethnicities. DOI: 10.5007/1980-0037.2011v13n4p243 - Diana Aguiar Santos; Analiza Mónica Silva; Helena Santa-Clara; Catarina Nunes Matias; David A Fields; Luís Bettencourt Sardinha (Universidade Federal de Santa Catarina, 2011)
Cardiorespiratory fitness is an important health indicator in young people. The aim of this study was to investigate the effects of age, gender, body adiposity, and ethnicity on cardiorespiratory fitness in a sample of Portuguese adolescents. The sample consisted of 266 adolescents aged 12-18 years [112 boys (80 Caucasians and 32 African-Portuguese, AP) and 154 girls (109 Caucasians and 45 AP)]. Percent body fat was estimated with a hand-to-hand bioelectrical impedance device (BF300, OMROM). Cardiorespiratory fitness was assessed by a shuttle run test (Fitnessgram battery). Multiple regression models were used for statistical analysis. The results showed that girls presented lower maximal oxygen consumption and higher percent body fat than boys. Cardiorespiratory fitness was lower in Caucasian than in AP girls. Multiple regression analysis showed that percent body fat, age and the interaction of age with being Caucasian and age with female gender were significant determinants that were negatively associated with cardiorespiratory fitness. The results suggest that maximal oxygen consumption is lower in adolescents with higher adiposity and in older adolescents. The findings highlight the importance of promoting physical fitness in schools across ages, especially in older adolescents, adjusting for determinant factors such as gender and ethnicity